The Age of Surveillance Capitalism: The Fight for a Human Future at the New Frontier of Power, S. Zuboff (2018). (1st June 2019) - Haggart, Blayne
New York: Public Affairs, 704 pp., ISBN 978-1-61039-569-4, h/bk, USD 38.00